STRATEGI BPBD KABUPATEN PACITAN DALAM UPAYA PENANGGULANGAN BENCANA BANJIR DAN TANAH LONGSOR - Sania Suci Ramadhani; Yusuf Hilman (Badan Penelitian dan Pengembangan Daerah Kota Samarinda, 2022)
This study aims to determine the condition of natural disasters such as floods and landslides and the efforts of BPBD to overcome them. The research was conducted in Pacitan City on the basis of the consideration that floods and landslides are common in this area. Data was collected through open interviews, observation, and document review, then the data were analyzed descriptively qualitatively. The results showed that the condition of the Pacitan City area consists mostly of highlands in the form of steep mountains and shallow river areas so that it is very vulnerable to natural disasters in the form of floods and landslides, especially during the rainy season. The flood natural disaster that occurred in Pacitan City was mainly caused by the silting of the riverbed and the narrowing of the river's width. Meanwhile, landslides are caused by erosion caused by rainwater and the increasing number of residential areas that make the foot of the slope increasingly eroded. Efforts made by BPBD to overcome natural disasters of floods and landslides that occurred in Pacitan Regency were by launching various forms of strategies such as the DESTANA program, Socialization, Procurement of Disaster Simulations, Construction of Embankments, Installation of Information Signs for Disaster-Prone Areas, Map-making of Disaster-Prone Areas and Determination of Evacuation Areas, and Mangrove Planting. The various strategies implemented also serve to increase public awareness and preparedness for disasters.